(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The research is aimed to explore the case study of salary for academician in education industry in comparison towards the benchmark within the overall job employment market in Malaysia. With the rising trend of the business, the job market had been increasing competitive within the employment market. Based on initial understandings, there are multiple suggestion that the compensation package for academicians appear to be less attractive against the compensation from other industries in a non-academician role for the job. With this, the designation of the quantitative study had addressed the comparative analysis using the salary guide to demonstrate the historical salary trend for education industry for the academicians against the accounting and finance related roles in four different industries namely, manufacturing, IT, retail and healthcare. The outcome through the findings had provide solid evidence where the results suggested that IT industry provide the highest compensation package to the individuals where the education industry for academicians appear to be setting lower average against the benchmark agreeing with the initial expectations for the study. The outcome of the study will provide significant drive to understand the needs for the education industry to further develop the revision on the salary compensation package for the academicians to improve the retention of the talents and skills for the teaching force in educational institutions in Malaysia.